Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/php.12459
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Concentration of Sodium Hypochlorite in Root Canal Irrigation by Combination of Ultrasonic Irrigation with Photodynamic Treatment

Abstract: Concentration of sodium hypochlorite (NaOCl) is positively correlated with its effectiveness in root canal disinfection but negatively correlated with its biocompatibility. The objective of this in vitro study was to compare the bactericidal effects among ultrasonic irrigation with different concentration of NaOCl alone or together with photodynamic treatment (PDT) against Enterococcus faecalis (E. faecalis) in infected root canals. One hundred and twenty bovine root canals contaminated with E. faecalis were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…As expected, 3% NaOCl had the best final outcomes. In fact, NaOCl at different concentrations, is considered an excellent irrigant solution in endodontics (Jeansonne and White, 1994; Siqueira et al, 2007; Mohammadi, 2008), nevertheless it also displays high toxicity levels toward the host tissues (Estrela et al, 2002; Önçaǧ et al, 2003; Trevino et al, 2011; Wang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, 3% NaOCl had the best final outcomes. In fact, NaOCl at different concentrations, is considered an excellent irrigant solution in endodontics (Jeansonne and White, 1994; Siqueira et al, 2007; Mohammadi, 2008), nevertheless it also displays high toxicity levels toward the host tissues (Estrela et al, 2002; Önçaǧ et al, 2003; Trevino et al, 2011; Wang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In the endodontic field, aPDT has emerged as an optional extra to classical irrigation solutions in root canal asepsis (Bonsor et al, 2006a,b) such as sodium hypochlorite (NaOCl), chlorhexidine gluconate (CHX) and ethylenediamine tetraacetic acid (EDTA). The NaOCl solution is the most widely used in endodontic treatment (Siqueira et al, 2007; Mohammadi, 2008; Vaziri et al, 2012; Wang et al, 2015) albeit with some degree of toxicity. To avoid this toxicity, other root canal asepsis approaches with lower or insignificant toxicity should be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…14 Therefore, there have been several alternative approaches proposed to improve the effectiveness of lower-concentration NaOCl solutions to avoid extensive tissue damage; however, these options have many limitations, including the requirement of inconvenient equipment. [15][16][17][18][19] Since eDNA is an essential component of E. faecalis biofilm, it can be speculated that its inhibition using a simple agent can be another strategy for effective biofilm removal. However, to our knowledge, there has been little information regarding the effect of eDNA on E. faecalis biofilm in endodontic study models.…”
Section: Introductionmentioning
confidence: 99%
“…In category I, 16 in vitro studies, only 5 (31%) [ 57 61 ] reveal best antimicrobial PDT outcomes when compared with sodium hypochlorite (NaOCl) in range of 0.5 to 6%. Only one study performed by Nagayoshi et al [ 62 ] reveals equal results between PDT and NaOCl; the remaining 10 (62.5%) studies [ 63 72 ] showed PDT outcomes unhelpful when compared with NaOCl as a classical irrigant solution, in concentration range of 0.5 to 6%. In category II, 6 (21%) papers [ 35 , 58 , 73 76 ] were analysed ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%